Across the sub-Arctic of Canada, a journey of 3,200 miles by canoe and snowshoe through the barren lands - Tyrrell, J. W. (James Williams), 1863-1945.; Heming, Arthur Henry Howard, 1870-1940. (Toronto, W. Briggs, 1897)
Mode of access: Internet.